2019
DOI: 10.1177/0036850419877766
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling photoprotection in microbial natural products

Abstract: Mycosporine-like amino acids have long been known as a natural form of photoprotection for fungi and cyanobacteria. This review will highlight the key time-resolved experimental and theoretical techniques unravelling their photochemistry and photophysics, and directly link this to their use in commercial skin-care products, namely as sunscreen filters. Three case studies have been selected, each having aided advancement in this burgeoning field of research. We discuss these studies in the context of photoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…We begin the mycosporine discussion by reviewing work conducted by Losantos et al [ 89 ] and Woolley et al [ 85 ] on basic cyclohexenone structures, herein referred to as mycosporine motifs. Further details of these authors’ works can be found in the reviews by Holt and Stavros [ 55 ] and Woolley and Stavros [ 83 ]. As a result, only a brief review will be given here.…”
Section: Case Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…We begin the mycosporine discussion by reviewing work conducted by Losantos et al [ 89 ] and Woolley et al [ 85 ] on basic cyclohexenone structures, herein referred to as mycosporine motifs. Further details of these authors’ works can be found in the reviews by Holt and Stavros [ 55 ] and Woolley and Stavros [ 83 ]. As a result, only a brief review will be given here.…”
Section: Case Studiesmentioning
confidence: 99%
“…Their findings were that in both solvents, a persistent ESA was present at extended time delays, Δ t > 2.5 ns, and this was attributed to the trapped population of ACyO in the minimum of the S 1 PES [ 85 ]. As the TAS have been reviewed previously [ 55 , 83 ], no further details are given here. In addition to the TEAS experiments, Woolley et al [ 85 ] also conducted complementary CASSCF calculations on ACyO to calculate critical points along the S 1 PES.…”
Section: Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations